The Relationship between the Level of Knowledge and Dengue Prevention Efforts - Aurum Latifah Azzahra; Abi Muhlisin (Indonesian Journal of Global Health Research, 2025)
The bite of the Aedes aegypti mosquito is a means of spreading dengue fever. Population density, uncontrolled waste growth, and lack of knowledge about environmental sanitation are the main causes of dengue fever transmission. To prevent dengue fever, the 3M Plus method involves the elimination of mosquito nests (PSN), which includes minimizing the drying of bathtubs, sealing water reservoirs, recycling used items, applying larvicide powder to water reservoirs, using mosquito repellent and mosquito nets while you sleep, and planting mosquito repellent plants. The purpose of this study is to ensure the level of public awareness and the way the people of Klari village, Karanggede Regency, prevent dengue disease. Methods: This study was carried out in Klari village, Karanggede district in September 2024 with a total of 78 respondents by purposive sampling. Data collection was carried out using a questionnaire with two types of instruments, including the level of knowledge and prevention efforts. Data analysis using the Chi-Square test. The results of the study showed two variables with a p < value of 0.05 on the non-parametric test, namely age, education level, and occupation. Results: The analysis of the Chi-Square test produced a p value of 0.1055 > 0.05. Conclusion: There is no relationship between the level of knowledge and dengue prevention efforts in Klari village, Karanggede district.